2022
DOI: 10.24912/jmieb.v6i1.15082
|View full text |Cite
|
Sign up to set email alerts
|

How Servqual and Visitor Satisfaction Affect Loyalty and Positive Wom Within the Indonesian Hotel Sector?

Abstract: Sektor perhotelan merupakan salah satu sektor ataupun industri yang sangat terdampak negatif oleh adanya pandemi COVID-19 yang saat ini terjadi dan melanda hampir seluruh belahan bumi di dunia, termasuk Indonesia. Namun, penurunan jumlah kasus positif COVID-19 di Indonesia yang terjadi akhir-akhir ini telah kembali “menghidupkan” para hotel ini, yang dimana, hal ini ditandai dengan kembali meningkatnya jumlah individu yang berkunjung ataupun menginap di berbagai hotel di Indonesia. Alhasil, maka penting bagi s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Therefore, it could be concluded that there will be no purchase decision (or purchase activities) if there's no intention to purchase the product at the first place. Purchase intention itself could be theoretically understood as consumers' strong willingness to buy, use, consume, or purchase certain products or services for various reasons, in which, with sufficient or adequate number of resources, such intention could (and will) turn into actual purchase decision or behavior (Yulita and Hidajat, 2021;Wilson, 2021;Gupta et al, 2022;Wilson and Goldie, 2022).…”
Section: Purchase Intentionmentioning
confidence: 99%
“…Therefore, it could be concluded that there will be no purchase decision (or purchase activities) if there's no intention to purchase the product at the first place. Purchase intention itself could be theoretically understood as consumers' strong willingness to buy, use, consume, or purchase certain products or services for various reasons, in which, with sufficient or adequate number of resources, such intention could (and will) turn into actual purchase decision or behavior (Yulita and Hidajat, 2021;Wilson, 2021;Gupta et al, 2022;Wilson and Goldie, 2022).…”
Section: Purchase Intentionmentioning
confidence: 99%